Spatio-temporal expression of MMP-2, MMP-9 and tissue kallikrein in uteroplacental units of the pregnant guinea-pig (Cavia porcellus) - Rey Sergio; Corthorn Jenny; Chacón Cecilia; Valdés Gloria (BMC, 2007)
Abstract Background In humans trophoblast invasion and vascular remodeling are critical to determine the fate of pregnancy. Since guinea-pigs share with women an extensive migration of the trophoblasts through the decidua and uterine arteries, and a haemomonochorial placenta, this species was used to evaluate the spatio-temporal expression of three enzymes that have been associated to trophoblast invasion, MMP-2, MMP-9 and tissue kallikrein (K1). Methods Uteroplacental units were collected from early to term pregnancy. MMP-2, MMP-9 and K1 were analysed by immunohistochemistry and Western blot. The activities of MMP-2 and MMP-9 were assessed by gelatin zymography. Results Immunoreactive MMP-2, MMP-9 and K1 were detected in the subplacenta, interlobar and labyrinthine placenta, syncytial sprouts and syncytial streamers throughout pregnancy. In late pregnancy, perivascular or intramural trophoblasts expressed the three enzymes. The intensity of the signal in syncytial streamers was increased in mid and late pregnancy for MMP-2, decreased in late pregnancy for MMP-9, and remained stable for K1. Western blots of placental homogenates at days 20, 40 and 60 of pregnancy identified bands with the molecular weights of MMP-2, MMP-9 and K1. MMP-2 expression remained constant throughout gestation. In contrast, MMP-9 and K1 attained their highest expression during midgestation. Placental homogenates of 20, 40 and 60 days yielded bands of gelatinase activity that were compatible with MMP-2 and MMP-9 activities. ProMMP-2 and MMP-9 activities did not vary along pregnancy, while MMP-2 and MMP-9 increased at 40 and 40-60 days respectively. Conclusion The spatio-temporal expression of MMPs and K1 supports a relevant role of these proteins in trophoblast invasion, vascular remodeling and placental angiogenesis, and suggests a functional association between K1 and MMP-9 activation.